The Implementation of PBL (Problem Based Learning) Model Assisted by Monopoly Game Media in Improving Critical Thinking Ability and Self Confidence - Indriani, Mikke Novia; Isnarto, Isnarto; Mariani, Scolastika (Journal of Primary Education, 2019)
This study aimed to describe the quality of PBL learning assisted by monopoly games on students 'critical thinking skill, and describing students' critical thinking skills through PBL learning assisted by monopoly game in terms of self-confidence. This study used mixed methods with concurrent embedded designs. The research subjects were seventh grade students of SMP N 18 Semarang. The results of this study showed that implementation PBL assisted by monopoly game improve the students’ mathematical critical thinking skills. In the aspect of the process of mathematical critical thinking skills, students with high self-confidence are able to master the five aspects very well. The five indicators of critical thinking are elementary clarification skills, basic skills building skills, inference skills, advanced clarification skills, and strategies and techniques. Students with medium self-confidence, mastering four aspects maximally, those are skills to give simple explanations, inference skills, advanced clarification skills, and strategies and techniques. Meanwhile, students with low self-confidence, only able to master one aspect well but not maximally that is ability to give a simple explanation (elementary clarification).